Performance Analysis with Quality Function Method Deployment (QFD) - Mahendrata, Ananda Juliano; Isradi, Muhammad (Journal of Educational Management Research, 2025)
Reliable and efficient public transportation is vital for urban areas like Semarang. This study evaluates the operational and service performance of Corridor 1, measures passenger satisfaction, and identifies service indicators needing improvement. Primary data were collected through field surveys and questionnaires distributed to 100 respondents. The methods used include Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), and Quality Function Deployment (QFD), referring to national and local transportation standards. Findings show that load factors (42% morning, 37% afternoon), bus speeds (25–27 km/h), and waiting times (3.6–3.8 minutes) meet service standards, while headways (7.3–7.6 minutes) remain outside the 2–5 minute peak-hour standard. In the afternoon, only 96% of the fleet operates. Based on IPA and QFD results, seven service indicators are prioritized for improvement: dwell time, onboard cleanliness and health facilities, heat-protective window film, accessibility to stops, user willingness to recommend the service, and passenger waiting times. The implications of this research for educational management are the importance of efficient public transportation to improve accessibility and comfort for students and educators. By improving service indicators, it is expected to support smooth mobility to educational institutions, increase student participation, and support active involvement in academic activities.